Binding of Streptococcal Competence Factor by the Spheroplast Membrane of a Group H Streptococcus - Perry, Dennis (1974)
The binding of streptococcal competence factor (CF) was found to be specific for a strain of streptococcus which was capable of undergoing competence induction. Three other streptococcal strains which could not be induced to competence, did not bind CF. CF binding was independent of time, temperature, age of the culture, and type of growth media employed. Several observations indicated that the receptor sites for CF are located in the bacterial membrane: (i) the retention of CF by spheroplasts, (ii) the binding of CF by isolated membrane fractions, and (iii), the degradation of CF binding capacity of membranes by different chemicals and enzymes.